Teknik Sablon sebagai Media Apresiasi Karya Desain pada Tshirt - Muhammad Imam Tobroni (Bina Nusantara University, 2011)
Screen printing is one of printing techniques. It has its own characteristic and uniqueness in the printing process, so it has customer likeability. Besides as printing media, screen printing is a media to promote and to gather creative ideas in reproduction printing technique. Communication could be understood as message, idea or information delivery process to other people that using specific facilities or equipment to influence or change the receiver’s behavior. T-Shirt as one message delivery media has important part in creative industry. Screen printing technique has different characteristic. T-Shirt as screen printing media is highly effective in supporting promotion and design work appreciation media.